Implementasi Kebijakan Kartu Indonesia Sehat (KIS) Di Desa Hegarmanah Kecamatan Sagaranten Kabupaten Sukabumi - Riansyah, Dede (Jurnal Administrasi Publik dan Pemerintahan, 2025)
Welfare can be a person's basic right and one of the welfare needs that must be realized in accordance with the beliefs of the Indonesian state. The government has made various efforts to improve the quality of community welfare. The Healthy Indonesia Card (KIS) program is expected to provide health protection to the community in terms of free health office services. This investigation aims to determine the use of the KIS Program Approach in Hegarmanah City. The theory used in this research is Edward III's hypothesis in Anggara (2018: 250) with specific measurements of Communication, Assets, Mien, Bureaucratic Structure. The method used can be a graphic strategy with a subjective approach, the rebels used in this investigation are meeting guides, cell phones, cell phone cameras, notebooks.The results of the research on the implementation of the KIS policy are seen from the communication aspect as not going well, from the aspect of resources being inadequate, from the aspect of disposition not being right, and from the aspect of bureaucratic structure it is already organized. It can be interpreted that the research conclusion on the implementation of the KIS policy in Hegarmanah Village has not been achieved.